A new species of Paraboea (Gesneriaceae) from a karst limestone hill in southwestern Guangdong, China - Wen, Fang; Hong, Xin; Chen, Ling-Yun; Zhou, Shou-Biao; Wei, Yi-Gang (Phytotaxa, 2013)
A new species of Gesneriaceae, Paraboea tetrabracteata, growing in rocky crevices on a limestone hill in Guangdong, China, is described and illustrated. It is morphologically similar to P. rufescens and P. dictyoneura in leaf and flower shape, but can be distinguished by undulate to faintly sinuate blade margins, 3–6 lateral veins on each side, petioles 0.4–1.3 cm, peduncles 4–9 cm, 4 narrowly oblong-ovate bracts, calyx narrowly oblong to lanceolate or linear, a purplish corolla tube, 2 staminodes and straight fruits.